Cultivating Slow Curating in Times of Acceleration - Alice Semedo; Fabiana Dicuonzo (Land)
This paper introduces key ideas and issues in the changing debates on heritage practices and sustainability. It draws attention to the capacities of heritage to activate and unfold new meanings and increase the resilience of territories and landscapes—namely depopulated ones—through slow curating processes. We will argue that slow curating processes cultivate ‘slower’ ways of knowing, act as seedbeds of emergence and as catalysts to transformation that recuperate the pieces of a fragmented territory while also helping to re-locate its existence—its past, its present and its future—in balance with and within a constellation of living networks. Through heritage criticality, we will investigate territory interpretation and intervention examples that adopt disruptive, cross-, inter-, and trans-disciplinary approaches, including artistic, architectural, urban, performative, and curatorial practice, as effects and methods of slow curating taken as a public activity. We will pay special attention to its production contexts (reasons, subjects…), to what and how resonance dispositions and axes are produced within these non-linear public acts, and how the co-presence of past and the future is extended so heritage public acts may engender new forms—of knowledge, being…—and become a resource for current times.